Exploration of Nitrate Reductase Metabolic Pathway in Corynebacterium pseudotuberculosis - Sintia Almeida; Cassiana Sousa; Vinícius Abreu; Carlos Diniz; Elaine M. S. Dorneles; Andrey P. Lage; Debmalya Barh; Vasco Azevedo (International Journal of Genomics)
Based on the ability of nitrate reductase synthesis, Corynebacterium pseudotuberculosis is classified into two biovars: Ovis and Equi. Due to the presence of nitrate reductase, the Equi biovar can survive in absence of oxygen. On the other hand, Ovis biovar that does not have nitrate reductase is able to adapt to various ecological niches and can grow on certain carbon sources. Apart from these two biovars, some other strains are also able to carry out the reduction of nitrate. The enzymes that are involved in electron transport chain are also identified by in silico methods. Findings about pathogen metabolism can contribute to the identification of relationship between nitrate reductase and the C. pseudotuberculosis pathogenicity, virulence factors, and discovery of drug targets.